Study on Local-Structure Symmetrization of K2XF6 Crystals Doped with Mn4+ Ions by First-Principles Calculations - Novita, Mega; Ristanto, Sigit; Saptaningrum, Ernawati; Supriyadi, Slamet; Marlina, Dian; Rondonuwu, Ferdy Semuel; Chauhan, Alok Singh; Walker, Benjamin; Ogasawara, Kazuyoshi; Piasecki, Michal; Brik, Mikhail G. (MDPI, 2023)
The crystals of Mn4+-activated fluorides, such as those of the hexafluorometallate family, are widely known for their luminescence properties. The most commonly reported red phosphors are A2XF6: Mn4+ and BXF6: Mn4+ fluorides, where A represents alkali metal ions such as Li, Na, K, Rb, Cs; X=Ti, Si, Ge, Zr, Sn, B = Ba and Zn; and X = Si, Ge, Zr, Sn, and Ti. Their performance is heavily influenced by the local structure around dopant ions. Many well-known research organizations have focused their attention on this area in recent years. However, there has been no report on the effect of local structural symmetrization on the luminescence properties of red phosphors. The purpose of this research was to investigate the effect of local structural symmetrization on the polytypes of K2XF6 crystals, namely Oh-K2MnF6, C3v-K2MnF6, Oh-K2SiF6, C3v-K2SiF6, D3d-K2GeF6, and C3v-K2GeF6. These crystal formations yielded seven-atom model clusters. Discrete Variational Xα (DV-Xα) and Discrete Variational Multi Electron (DVME) were the first principles methods used to compute the Molecular orbital energies, multiplet energy levels, and Coulomb integrals of these compounds. The multiplet energies of Mn4+ doped K2XF6 crystals were qualitatively reproduced by taking lattice relaxation, Configuration Dependent Correction (CDC), and Correlation Correction (CC) into account. The 4A2g→4T2g (4F) and 4A2g→4T1g (4F) energies increased when the Mn-F bond length decreased, but the 2Eg → 4A2g energy decreased. Because of the low symmetry, the magnitude of the Coulomb integral became smaller. As a result, the decreasing trend in the R-line energy could be attributed to a decreased electron–electron repulsion. © 2023 by the authors. --//-- Novita M., Ristanto S., Saptaningrum E., Supriyadi S., Marlina D., Rondonuwu F.S., Chauhan A.S., Walker B., Ogasawara K., Piasecki M., Brik M.G.; Study on Local-Structure Symmetrization of K2XF6 Crystals Doped with Mn4+ Ions by First-Principles Calculations; (2023) Materials, 16 (11), art. no. 4046; DOI: 10.3390/ma16114046; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85161550468&doi=10.3390%2fma16114046&partnerID=40&md5=678d718c6d981206bbf94172d3a4bc64 published under the CC BY 4.0 licence.
We appreciate the support of our students who helped this research, i.e., Joko Setiawan (Magister of Science Education, Universitas PGRI Semarang), and Ammar Amjad (Department of Informatics, Universitas PGRI Semarang).
Keywords: Research Subject Categories::NATURAL SCIENCES; A2BF6; fluorides; hexafluorometallate; luminescence; Mn4+; phosphor